PENGARUH LATIHAN MENENDANG SEMBILAN BOLA KE GAWANG TERHADAP KETEPATAN SHOOTING PADA TIM SSB KUANSING SOCCER SCHOOL - Siswanto, Robi; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The problem in this research is that their shooting ability is still belowaverage, and perhaps this is also the reason why they often lose in matches. The aim ofthis research was to determine the effect of training in kicking nine balls into the goal onshooting accuracy on the SSB Kuansing Soccer School team. The method used in thisresearch is the experimental method. The research design carried out in this study was